Endoscopic Characteristics of Early Gastroesophageal Junction Adenocarcinomas and Assessment for Invasion Depth: A Case Series Study - Song, Shunzhe; Yan, Feng; Zhang, Jingwen; Gong, Aixia (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Early-stage gastroesophageal junction (GEJ) adenocarcinoma can be challenging to diagnose and treat promptly using endoscopy. This study aims to summarize the endoscopic characteristics of early GEJ adenocarcinoma and investigate their cor relation with pathological grade and invasion depth. Materials and Methods: This retrospective case series study evaluated patients with early GEJ adenocarcinoma who underwent endo scopic or surgical resection at First Affiliated Hospital of Dalian Medical University between January 2016 and December 2022. Results: A total of 71 patients were included in the analysis, with 59 males and a median age of 67 years. The majority of the lesions were located on the posterior side of the GEJ (40.8%) or the lesser curvature side (29.6%). Siewert II lesions accounted for 71.8% of cases, with most occurring on the posterior side (49.0%) and Siewert III lesions mostly occurring on the lesser curvature side (42.9%). Siewert I lesions accounted for only 7.0%, and all originated from Barrett mucosa. Paris classification of Is (P = .015) or IIc (P = .015), lesion size ≥12 mm (P = .017), red color with subsquamous extension (P = .038), and disordered microsurface with local fusion (P < .001) were inde pendently and positively correlated with pathological grade and invasion depth by multivariable ordinal logistic regression. Conclusion: The posterior side and lesser curvature of the GEJ are the high-incidence sites of GEJ adenocarcinoma. Both forward and backward views during endoscopy should be combined to detect the lesion. Endoscopic characteristics such as Is or IIc morphology, larger size, red color with subsquamous extension, and disordered microsurface with local fusion may indicate a higher pathological grade and deeper invasion. Cite this article as: Song S, Yan F, Zhang J, Gong A. Endoscopic characteristics of early gastroesophageal junction adenocarcinomas and assessment for invasion depth: A case series study. Turk J Gastroenterol. 2024;35(1):11-16.